On the exploitation of dynamic simulations for the design of buildings energy systems - Kotarela, Faidra; Kyritsis, Anastasios Ch.; Agathokleous, Rafaela; Papanikolaou, Nick P. (My University, 2023)
To achieve the Paris Agreement 1.5 °C target, apart from the obligation for new buildings to be ZEBs, the existing building stock should be retrofitted as well, in order to improve their energy efficiency by using more efficient electromechanical energy systems and envelope materials, whereas RES should cover their energy needs. In this context, Energy Performance Certificates (EPCs) have been institutionalized to certify the energy behavior of buildings. Various types of buildings energy modeling tools and calculation methods have been proposed for EPCs procedures. This study focuses on the energy performance gap between dynamic and quasi steady-state simulation tools. The results from a comparative case study have shown remarkable discrepancies between dynamic and quasi-steady-state simulation processes, for the same building. Indeed, the quasi-steady-state simulation tool estimates 4.5% higher annual electricity consumption per conditioned area for the existing building and approximately 74% less energy savings for the retrofitted one, leading to an overestimation of 85% in CO2 emissions prediction. Finally, compared to the analysis with the dynamic simulation tool, an increased retrofit cost, approximately by 19.7% (and thus 3 times higher payback period), is needed according to the results of the quasi-steady-state simulation tool, in order to achieve the same Energy classification.
Keywords: Building energy consumption; Building retrofit; Building simulation tools; Energy performance certificates; Energy saving potentia; Renewable energy sources